Zoo - Patterson, James 1947-; Ledwidge, Michael; Snyder, Jay. (New York : Hachette Audio, 2012)
As coordinated attacks by animals against humans increase and escalate, young biologist Jackson Oz and ecologist Chloe Tousignant warn world leaders that soon there will be nowhere left for humans.
Unabridged.
Compact discs.
Read by Jay Snyder.
Keywords: Aggressive behavior in animals -- Fiction; Human-animal relationships -- Fiction; Biologists -- Fiction; Ecologists -- Fiction; Suspense fiction; Audiobooks